Sale of critically endangered sharks in the United States - Ryburn, Savannah J.; Yu, Tammy; Ong, Kelly J.; Wisely, Eldridge; Alston, Meggan A.; Howie, Ella; LeRoy, Peyton; Giang, Sarah Elizabeth; Ball, William; Benton, Jewel; Calhoun, Robert; Favreau, Isabella; et al. (Frontiers in Marine Science, 2025)
In the United States, shark meat is sold in grocery stores, seafood markets, and online. The meat is often mislabeled as another species or generically labeled as “shark”. The ambiguity of these generic labels makes it challenging to assess the conservation implications of this practice and for consumers to avoid high trophic-level species that often have high mercury concentrations in their tissues. We purchased and DNA barcoded 29 shark products in the United States to determine their species identity. Our samples consisted of 19 filets sold in grocery stores, seafood markets, and Asian specialty markets (mostly in North Carolina) and 10 ordered online as “jerky”. Ninety three percent of samples (27 of 29) were ambiguously labeled as shark or mako shark but not as a specific species. Of the two samples that were labeled to species, one was mislabeled (e.g., shortfin mako shark labeled as blacktip shark) and the other was correctly labeled. Barcoding indicated that the 29 samples included 11 different species of shark, including three species listed by the IUCN as Critically Endangered: great hammerhead, scalloped hammerhead, and tope. Previous studies have found that the first two species contain very high levels of mercury, illustrating the implications of seafood mislabeling for human health. The availability of shark meat in U.S. grocery stores is surprising given the dramatic decline of shark populations globally. Moreover, the fact that nearly all shark meat is labeled ambiguously or incorrectly amplifies the problem. Accurate, verified product labels for shark meat would benefit consumers and shark conservation efforts, and should be a priority for the seafood industry.